Evaluasi Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) PT.X Industri Rokok Tembakau - SN, Achmad Aditiyo; Yusrianti; Auvaria, Shinfi Wazna; Setyowati, Rr Diah Nugraheni; Nilandita, Widya (Casuarina: Jurnal Teknik Lingkungan, 2024)
The aim of this research is to evaluate compliance with the applicable regulations. The research methods include data collection, both primary and secondary, field observations, and interviews with relevant parties, along with relevant literature as supporting material for this study. The findings of the research indicate that PT X has not yet implemented several hazardous waste (B3) management steps, including waste identification and sorting, temporary storage, as well as transportation and final waste processing. However, there are several challenges encountered, such as a lack of storage facilities meeting the standards, limitations in internal supervision, and a lack of employee awareness regarding the importance of proper hazardous waste management. This research recommends several improvements, such as upgrading storage facilities to meet standards, enhancing training and outreach programs for employees, and strengthening the supervision and monitoring system of hazardous waste management. The implementation of these recommendations is expected to improve the effectiveness of hazardous waste management at PT X and reduce negative impacts on the environment and the surrounding community's health.